Brill's companion to Aphrodite - Smith, Amy Claire, 1966-; Pickup, Sadie. (Brill's Companions to Classical Studies., 2010)
Brill's Companion to Aphrodite brings together an international and multidisciplinary team of experts in the study of Aphrodite-one of the best known, yet ambiguous and complex Graeco-Roman deities. The contributions, which reevaluate conventional approaches to this remarkable goddess, are thematically grouped in four parts according to aspects of the goddess: 'Aphrodite's Identity'; 'Aphrodite's Companions and Relations'; 'The Spread of Aphrodite's Cults' and 'The Reception of the Goddess.' Each part draws on literary and visual sources, incorporates Greek, Roman, and later material, and ranges across places and periods-from prehistoric Cyprus and the Near East to the antiquities market in 19th century France. This book therefore crosses interdisciplinary boundaries, as well as the multiple aspects and characteristics of the goddess